O Desenvolvimento Baseado em Conhecimento no Contexto das Cidades: Uma Análise do Caso de Monterrey - Fernanda Rizzon (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
As the economy migrated from essentially agricultural to industrial and commercial, accompanied by population growth, cities emerged as the initial model of a system of human and economic organization. Nowadays, the concepts of City of Knowledge emerge, since cities are no longer seen exclusively as economic-financial centers, but as a set of tangible and intangible values that relate to people, companies and governments in a triple propeller. With the purpose of examining the application of the concept of Knowledge City, this article presents a unique case study with the object of study being the Mexican city of Monterrey, considered an emerging knowledge city. The case of Monterrey reveals opportunities marked by the knowledge society, since it requires the mobilization of endogenous resources, just as the examples observed in this article show us the fact that the resources of knowledge already exist and have a kind of “ “In cultural and historical values, developed in an organic and unique way. Regarding the limitations of the study, it is important to consider the time cut restricted to 2008 and 2009, which limited the analysis of the case in relation to the most recent events, such as the installation of drug cartels in the city that shaken their plans and strategies. These recent events represent a perspective for the continuation of the study of the case of Monterrey oriented to the analysis of the impacts of violence and organized crime in its capital system.